The Influence of Brand Equity, Brand Ambassador, and Brand Trust on Purchase Decisions of Somethinc Consumers in Jakarta - Jessicha Tanujaya; Carunia Mulya Firdausy (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The demand for local skincare products in Jakarta has grown significantly, with Somethinc emerging as a key player in 2024. This study examines the impact of brand equity, brand ambassador, and brand trust on consumer purchase decisions for Somethinc products in Jakarta. A quantitative approach was employed, with data collected through an online questionnaire distributed to 384 respondents selected via purposive sampling (criteria: Jakarta residents aged 17–40 who purchased Somethinc products in the past year). The data were analyzed using partial least squares structural equation modeling (PLS-SEM) in SmartPLS 4 to assess the relationships between variables. The results reveal that all three factors—brand equity (β = 0.28, p < 0.01), brand ambassador (β = 0.22, p < 0.05), and brand trust (β = 0.35, p < 0.01)—positively and significantly influence purchase decisions, with brand trust exhibiting the strongest effect. These findings align with prior research emphasizing trust as a critical driver in the beauty industry, where perceived reliability and product efficacy are paramount. The study also highlights the role of local brand ambassadors in enhancing credibility and emotional connection with younger consumers. Practical implications suggest that Somethinc should prioritize long-term trust-building (e.g., transparency in ingredients, post-purchase engagement) and leverage ambassador partnerships to strengthen equity. Future research could explore cultural or generational moderators in other Indonesian regions.